Soaking grapevine cuttings in water: a potential source of cross contamination by micro-organisms - WAITE, Helen; GRAMAJE, David; WHITELAW-WECKERT, Melanie; TORLEY, Peter; HARDIE, W. Jim (Phytopathologia Mediterranea, 2012)
Grapevine nurseries soak cuttings in water during propagation to compensate for dehydration and promote root initiation. However, trunk disease pathogens have been isolated from soaking water, indicating cross contamination. Cuttings of Vitis vinifera cv. Sunmuscat and V. berlandieri x V. rupestris rootstock cv. 140 Ruggeri were immersed in sterilized, deionised water for 1, 2, 4, 8 and 16 h. The soaking water was cultured (25°C for 3 days) on non-specific and specific media for fungi and bacteria. The base of each cutting was debarked and trimmed and three 3 mm thick, contiguous, transverse slices of wood cultured at 25°C for 3 days. The soaking water for both cultivars became contaminated with microorganisms within the first hour. Numbers of fungi iso-lated from the wood slices soaked for one hour were significantly greater than those from non-soaked cuttings. The number of bacterial colonies growing from the wood slices increased after soaking for 2‒4 h in Sunmuscat. In a second experiment Shiraz cuttings were soaked for 1, 2, 4, 8 and 24 h. The soaking water became contaminated within the first hour but only the bacterial count increased significantly over time. Microorganisms also established on the container surfaces within the first hour although there were no significant increases over 24 h. These results confirm that soaking cuttings is a potential cause of cross contamination and demonstrate contamination of cuttings occurs after relatively short periods of soaking. Avoiding exposing cuttings to water will reduce the transmission of trunk diseases in propagation.